2019
DOI: 10.1016/j.jtherbio.2018.12.010
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a broad range of experimental temperatures on the population growth and body-size of five species of free-living nematodes

Abstract: Majdi N. et al. (2019) Effects of a broad range of experimental temperatures on the population growth and body-size of five species of free-living nematodes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 51 publications
3
13
0
Order By: Relevance
“…Therefore, we generally validated our assumption that it is justified to refer to thermal preference instead of thermal acclimation in our further interpretation of the results. Additionally, this result confirms the adaptive nature of body size linked to temperature at the interclonal level along with the previous interspecific patterns found for three species representing the Brachionus plicatilis cryptic species complex (Walczyńska and Serra 2014) and five species of free-living nematodes (Majdi et al 2019).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Therefore, we generally validated our assumption that it is justified to refer to thermal preference instead of thermal acclimation in our further interpretation of the results. Additionally, this result confirms the adaptive nature of body size linked to temperature at the interclonal level along with the previous interspecific patterns found for three species representing the Brachionus plicatilis cryptic species complex (Walczyńska and Serra 2014) and five species of free-living nematodes (Majdi et al 2019).…”
Section: Discussionsupporting
confidence: 89%
“…Our largest clone, also acclimated to intermediate temperature, exhibited the poorest performance of all (though best at the lowest temperature as relative to other clones). Regarding nematodes, the largest species showed notably poor growth in all other regimes compared with the other four species, although it had the highest fitness in the coldest temperature (Majdi et al 2019). These results are in contrast to previous reports (Geister and Fischer 2007; Kingsolver and Huey 2008) and show that larger sizes are not always better.…”
Section: Discussionmentioning
confidence: 99%
“…This is especially true in systems (like the MDV) where limited biodiversity and strong abiotic gradients can make interactions more detectable. Future research should verify the nature of the associations highlighted in this paper, using in vitro studies; higher resolution molecular work (e.g., primer amplicon studies and deeper metagenome sequencing) that can improve taxonomic resolution from family and genus to species or even populations; controls for small-scale abiotic and spatial filtering effects (e.g., soil heterogeneity within a sample site and vertical soil structure); and culture-based assessments of environmental tolerances and feeding preferences [ 56 , 94 , 95 ]. Achieving these goals will lay the groundwork for characterizing the links between ecosystem functioning and biodiversity for an entire microbial soil community [ 16 ], and will facilitate an improved understanding of ecological processes within and beyond the MDV system.…”
Section: Discussionmentioning
confidence: 99%
“…The same difficulties were due to the scarcity of studies related to the "locomotion and substrate relation" trait which has been investigated almost exclusively in nematodes, rotifers, some crustaceans and gastrotrichs e.g., [55,56]. Majdi et al [21] suggested using laboratory populations with mesocosms to study certain traits that otherwise would not be directly observable in the field e.g., [57,58].The results obtained also indicate that the traits receiving the least interest are respiration and thermal preference. These traits, on the other hand, require an indepth study, especially considering the future climate change scenarios that will dramatically affect the coastal areas of lakes [59,60].…”
Section: Discussionmentioning
confidence: 99%